A compact, high-flux source of cold atoms - Ravenhall, S (2018)
The ongoing drive to transfer quantum technologies from research laboratories to practical, portable devices requires the development of multiple key enabling technologies. The field of cold atoms, which includes high-precision metrology and quantum simulation, has various real-world applications including time-keeping and navigation. A crucial component in these systems is a cold-atom source that generates a flux of low-velocity atoms suitable for subsequent capture. A large flux enables fast repetition rates, high duty cycles, long measurement times, and resistance to long-term performance degradation with a good signal-to-noise ratio, all of which are essential to produce cold-atom devices and technologies that are capable of out-performing the classical alternatives. This thesis presents the design, fabrication and characterisation of a novel cold-atom source using a compact pyramidal magneto-optical trap (MOT) with a unique adjustable-aperture mechanism. This allowed an investigation of the dependence of the flux characteristics on the aperture size, a parameter space that has not previously been explored. The measurements showed a strong dependence of the flux on the aperture size, with a negligible flux below 0.4mm, then an approximately linear increase up to 1.0mm, at which point the relationship showed possible signs of saturation. Using 87Rb, a flux of 1.18×1010 atoms/s was produced using a 1.27mm aperture, for which the mean velocity of the atoms was 21.6(3) m/s with a FWHM of 11.2(2) m/s, and the FWHM divergence of the beam was 86(2) mrad. This is the highest recorded flux from a pyramid or 2D+-MOT source, and amongst the highest reported fluxes from any MOT sources, and avenues for improvement still remain. This work fulfils the aim of demonstrating a compact and robust cold-atom source generating a high flux of laser-cooled atoms for real-world quantum technology applications.